Vernier frequency division with dual-microresonator solitons - Beichen Wang (Nature Portfolio, 2020)
For advanced microcomb applications, the exact detection of the high repetition rate becomes difficult due to the limited bandwidth of the photodiodes. Here, the authors present a Vernier dual-comb method to sample the main soliton comb and divide the repetition rate by a generating low frequency beat notes.